Frequent IgE recognition of Blomia tropicalis allergen molecules in asthmatic children and young adults in equatorial Africa - Pauli, Gabrielle; Wurmser, Carole; Roos, Antoine; Kokou, Cosme; Huang, Huey-Jy; D’souza, Nishelle; Lupinek, Christian; Zakzuk, Josefina; Regino, Ronald; Acevedo, Nathalie; Caraballo, Luis; Vrtala, Susanne; et al. (Frontiers in Immunology, 2023)
Asthma is not well investigated in equatorial Africa and little is known about the disease-associated allergen molecules recognized by IgE from patients in this area. The aim was to study the molecular IgE sensitization profile of asthmatic children and young adults in a semi-rural area (Lambaréné) of an equatorial African country (Gabon), to identify the most important allergen molecules associated with allergic asthma in equatorial Africa. Fifty-nine asthmatic patients, mainly children and few young adults, were studied by skin prick testing to Dermatophagoides pteronyssinus (Der p), D. farina (Der f), cat, dog, cockroach, grass, Alternaria and peanut. Thirty-three of the 59 patients (56%) were sensitized to Der p and 23 of them (39%) were also sensitized to other allergen sources, whereas 9 patients (15%) were only sensitized to allergen sources other than Der p. Sera were obtained from a subset of 35 patients, 32 with positive and 3 with negative skin reaction to Der p and tested for IgE reactivity to 176 allergen molecules from different allergen sources by ImmunoCAP ISAC microarray technology and to seven recombinant Blomia tropicalis (Blo t) allergens by IgE dot blot assay. High IgE-binding frequencies were found for the Blo t allergens Blo t 5 (43%), Blo t 21 (43%) and Blo t 2 (40%), whereas the most frequently recognized Der p allergens were Der p 2, Der p 21 and Der p 5 (34%, 29% and 26%). Only few patients showed IgE reactivity to allergens from other allergen sources, except to allergens containing carbohydrate determinants (CCDs) or to wasp venom allergens (i.e., antigen 5). Our results thus demonstrate that IgE sensitization to mite allergens is very prevalent in asthmatics in Equatorial Africa with B. tropicalis allergen molecules representing the most important ones associated with allergic asthma.